Pengaruh Service Experience terhadap Patient Loyalty melalui Perceived Value dan Patient Trust di RS Swasta XYZ di Kota Tangerang - Natasha Waya; Hendra Achmadi (Universitas Muhammadiyah Palembang, 2026)
Tight competition in Indonesia’s healthcare sector highlights the need for hospitals to strengthen patient loyalty. While perceived value and patient trust are recognized as key determinants, the mediating role of trust in the value–loyalty relationship remains understudied. This study examines the effect of service experience on perceived value, the effect of perceived value on patient loyalty, and the mediating role of patient trust among patients at RS SWASTA XYZ in Tangerang. Using a cross-sectional design and purposive sampling, respondents completed an online questionnaire measuring service experience, perceived value, trust, and loyalty. Data were analyzed using SEM-PLS. Results show that service experience significantly increases perceived value, and perceived value significantly enhances patient loyalty. Perceived value does not significantly influence patient trust. Patient trust strongly affects loyalty and significantly mediates the relationship between perceived value and loyalty. These findings highlight the central role of service experience and trust in shaping patient loyalty within private hospital settings.